Sleep in Children with Neurodevelopmental Disabilities - Angriman, Marco; Caravale, Barbara; Novelli, Luana; Ferri, Raffaele; Bruni, Oliviero (Neuropediatrics, 2015)
This review describes recent research in pediatric sleep disorders associated with neurodevelopmental disabilities (NDDs) and their treatment. NDDs affect more than 2% of the general population and represent more than 35% of the total cases of children referred to a neuropsychiatric center for sleep problems. Specific clinical and therapeutic aspects of sleep disorders associated with Down syndrome, Fragile X syndrome, Prader–Willi syndrome, Angelman syndrome, Rett syndrome, Smith–Magenis syndrome, cerebral palsy, and autism spectrum disorders are described. Furthermore, the drugs commonly used for sleep disorders in children with NDDs are described. The review clearly highlighted that children with NDDs are often affected by sleep disorders that require appropriate clinical and therapeutic approach to improve quality of life in both patients and families.
Keywords: sleep disorders; neurodevelopmental disabilities; Down syndrome; Fragile X syndrome; Prader–Willi syndrome; Angelman syndrome; Rett syndrome; Smith–Magenis syndrome; cerebral palsy; autism spectrum disorders